Serving Athena: The Festival of the Panathenaia and the Construction of Athenian Identities - Shear, Julia Louise (University of Cambridge ESOL Examinations, 2021)
Examines how the Panathenaia ('all Athenian'), the most important festival in ancient Athens, created identities for participants.